Pengaruh Transfer Pricing Terhadap Praktik Penghindaran Pajak Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2020-2023 - Hanifah, Ulfiana; Cepi Saepuloh (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
This research aims to determine the effect of Transfer Pricing on Tax Avoidance in Manufacturing companies listed on the IDX in 2020-2023. The population in this study are 16 manufacturing companies listed on the IDX in 2020-2023 using a purposive sampling technique and resulted 9 companies. The data source used is secondary data. The data collection technique is a documentation technique by examining the company’s financial reports via the Indonesia Stock Exchange website. Data were analyzed using the Classical Assumption Test, Regression Test, Correlation Test, Determination Test dan Hypothesis Test. Based on the results of data analysis, it is concluded that there is no influence of Transfer Pricing on Tax Avoidance Practices in Companies listed on the IDX in 2020-2023.